2017
DOI: 10.1016/j.jot.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage repair by mesenchymal stem cells: Clinical trial update and perspectives

Abstract: SummaryOsteoarthritis is a degenerative disease of joints with destruction of articular cartilage associated with subchondral bone hypertrophy and inflammation. OA is the leading cause of joint pain resulting in significant worsening of the quality-of-life in the elderly. Numerous efforts have been spent to overcome the inherently poor healing ability of articular cartilage. Mesenchymal stem cells (MSCs) have been in the limelight of cell-based therapies to promote cartilage repair. Despite progressive advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
142
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 122 publications
(137 reference statements)
3
142
0
1
Order By: Relevance
“…Due to their unique properties, ASCs hold promise in treating multiple disorders, including graft versus host disease, multiple sclerosis, diabetes mellitus and autoimmune‐induced diseases . Moreover, their application in bone and cartilage regeneration as well as wound healing was widely investigated . There has been a growing number of ASC‐related studies demonstrating the ability of these cells to decrease IR, promote regeneration of pancreatic beta cells and suppress autoimmunity in the course of diabetes …”
Section: Introductionmentioning
confidence: 99%
“…Due to their unique properties, ASCs hold promise in treating multiple disorders, including graft versus host disease, multiple sclerosis, diabetes mellitus and autoimmune‐induced diseases . Moreover, their application in bone and cartilage regeneration as well as wound healing was widely investigated . There has been a growing number of ASC‐related studies demonstrating the ability of these cells to decrease IR, promote regeneration of pancreatic beta cells and suppress autoimmunity in the course of diabetes …”
Section: Introductionmentioning
confidence: 99%
“…Some early studies suggest that intra‐articular injections of MSCs may be of benefit in OA of the knee, although it is unclear whether the MSCs result in cartilage regeneration or whether the anti‐inflammatory effect of MSCs may explain the observed clinical benefit . A recent systematic review of stem cell therapy in OA suggested that, although the published literature suggests a benefit of this MSC, there is limited high‐quality evidence and long‐term follow‐up for these therapies in OA …”
Section: Nonpharmacological Regenerative Medicine Approachesmentioning
confidence: 99%
“…Collagen is hyaline cartilage composed of 60% (by dry weight) chondrocytes. Fibrocartilage and elastic cartilage are two other types of cartilage differing in ECM and cell components [115].…”
Section: Articular Cartilage Rejuvenationmentioning
confidence: 99%
“…As the matrix decreases, articular cartilage becomes increasingly thin, the hydration of cartilage decreases, and the number of cartilage cells also decreases [115].…”
Section: Articular Cartilage Rejuvenationmentioning
confidence: 99%
See 1 more Smart Citation